2019
DOI: 10.1038/s41598-019-44327-8
|View full text |Cite
|
Sign up to set email alerts
|

In vitro NTPase activity of highly purified Pdr5, a major yeast ABC multidrug transporter

Abstract: The ABC transporter Pdr5 of S . cerevisiae is a key player of the PDR network that works as a first line of defense against a wide range of xenobiotic compounds. As the first discovered member of the family of asymmetric PDR ABC transporters, extensive studies have been carried out to elucidate the molecular mechanism of drug efflux and the details of the catalytic cycle. Pdr5 turned out to be an excellent model system to study functional and structural characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 53 publications
1
29
0
Order By: Relevance
“…In line with this notion, all purified cysteine mutants exhibited a stable basal ATPase activity, ruling out a direct effect on the functionality of the transporter. This basal activity is within the range of values reported for a number of other purified eukaryotic ABC transporters [ 26 , 27 , 28 , 29 , 30 ]. Two purified detergent-solubilized cysteine mutants (C1330S and C1333S) exhibited ~2-fold increased basal ATP activity.…”
Section: Discussionsupporting
confidence: 83%
“…In line with this notion, all purified cysteine mutants exhibited a stable basal ATPase activity, ruling out a direct effect on the functionality of the transporter. This basal activity is within the range of values reported for a number of other purified eukaryotic ABC transporters [ 26 , 27 , 28 , 29 , 30 ]. Two purified detergent-solubilized cysteine mutants (C1330S and C1333S) exhibited ~2-fold increased basal ATP activity.…”
Section: Discussionsupporting
confidence: 83%
“…With regards to the substrate affinity represented by the k half value, a minimum of 0.41 ± 0.05 mM was reached using ATP as a substrate, which signifies ATP as the most favoured of all four tested NTPs for SaNsrF WT . Hence, ATP has the highest affinity to SaNsrF WT compared to the other examined NTPs, which corresponds with the physiological appearance in vivo of each NTP ([ATP] > [GTP] > [UTP] > [CTP]), which underlines that ATP is the preferred substrate for the protein 32,[66][67][68] . Considering the physiology of purine (ATP, GTP) and pyrimidine (UTP, CTP) nucleotides, we concluded that the involved aromatic ring systems play a major role concerning the substrate affinity and stability of the protein-substrate-complex.…”
Section: Discussionmentioning
confidence: 89%
“…An interaction between the NBD and the nucleotide is supposed to occur by π–π-stacking between the aromatic ring system of the nucleotide and an aromatic residue of the protein (F or Y). Hence, no preference towards any nucleotide-triphosphate (NTP) has been assumed 24 , as also observed for example for yeast PDR5 32 . The hydrolysis of ATP is coupled to the presence of a cofactor, almost exclusively Mg 2+ , which is coordinated by the Walker B motif.…”
Section: Introductionmentioning
confidence: 79%
“…[32] demonstrated that the regulatory domains of both Pdr1 and Pdr3 bind the antifungal ketoconazole at low micromolar affinity, leading to the speculation that ligand binding may increase transcriptional activity. Characterization of Pdr1 mutants has also proven useful in the yeast membrane biology field as pdr1‐3 has proven an effective tool for overexpression, and hence biochemical study, of Pdr5 and other membrane proteins [33,34].…”
Section: The Role Of Master Regulators Pdr1 and Pdr3 In Multidrug Resmentioning
confidence: 99%